2004
DOI: 10.1021/jo049097o
|View full text |Cite
|
Sign up to set email alerts
|

Azolium-Linked Cyclophanes:  A Comprehensive Examination of Conformations by 1H NMR Spectroscopy and Structural Studies

Abstract: The synthesis and characterization of a series of azolium-linked cyclophanes are reported. The cyclophanes consist of two azolium groups (17 examples) or three imidazolium groups (1 example) linked to two benzenoid units (benzene, naphthalene, p-xylene, mesitylene, 1,2,3,4- and 1,2,4,5-tetramethylbenzene, 2,6-pyridine, and p-tert-butylphenol) via methylene groups. Cyclophanes containing ortho-, meta-, and para-substitution patterns in the benzenoid units were examined. The conformations of the cyclophanes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
102
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(107 citation statements)
references
References 27 publications
(48 reference statements)
4
102
0
1
Order By: Relevance
“…The results of the single-crystal X-ray studies of 2b (Figure S1), and 4-8 (see Figures 5,6,7,8,9, and 10; Tables 1, 2, 3, and 4) support the proposed formulations, with 2b, 6, 7, and 8 solvated in some manner. Compound 2b crystallised with one molecule of CHCl 3 per formula unit.…”
Section: Structure Determinationssupporting
confidence: 53%
See 1 more Smart Citation
“…The results of the single-crystal X-ray studies of 2b (Figure S1), and 4-8 (see Figures 5,6,7,8,9, and 10; Tables 1, 2, 3, and 4) support the proposed formulations, with 2b, 6, 7, and 8 solvated in some manner. Compound 2b crystallised with one molecule of CHCl 3 per formula unit.…”
Section: Structure Determinationssupporting
confidence: 53%
“…The bidentate NHCs consist of benzimidazolin-2-ylidene units that are linked by one o-xylyene group, and generally bind to the metal centre in a rigid fashion. [6,7] The benzimidazolin-2-ylidene units possess bulky substituents on the nitrogen atoms and electron donating butoxy groups on the arene ring, the latter which also serve to increase the solubility of the complexes in common organic solvents. We have previously reported the use of similar electron-rich benzimidazolin-2-ylidenes as ligands in a range of palladium complexes of mono-and bidentate NHC ligands possessing phosphane or pyridine ancillary ligands, [8,9] and are interested in extending this investigation by studying the differences in catalytic activity between the bis(NHC)PdX 2 and (NHC)Pd(allyl)X systems.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the intracellular concentration of this metal is tightly regulated by zinc transporters, which could be removing zinc from the fungal cells. 57,58 In general, complex (15) showed the highest antifungal effects and inhibited the growth of all tested Candida species and also A. fumigatus. Singh et al 16 reported .…”
Section: Antibacterial Activitymentioning
confidence: 95%
“…process (anti→anti exchange) was more facile than the benzene ring flip process (anti→syn exchange), and rate constants and activation energies for each process were estimated from the variable temperature NMR data (See the first entry in Table 1). 7 The benzimidazolium cyclophane 5.2Br displayed behavior similar to that of 3.2Br, including broad signals at room temperature, corresponding to the benzylic protons, that coalesced at higher temperatures. In general, the "non-alkylated" cyclophanes 3.2Br-5.2Br were very soluble in water, displayed low solubility in DMSO and methanol, and were insoluble in organic solvents of medium polarity such as acetone, chloroform and dichloromethane.…”
Section: Introductionmentioning
confidence: 96%